Iceland : Financial System Stability Assessment Update, including Report on the Observance and Standards and Codes on the following topics; Banking Supervision, Insurance Regulation, Securities Regulation, Payment Systems, and Monetary and Financial Policy Transparency. (IMF Staff Country Reports; Country Report ;, 2003)
The 2001 financial system stability assessment identified risks of financial sector instability, as rapid increases in foreign and domestic currency indebtedness, accumulating external imbalances, and inflation accompanied Iceland's expansion of the late 1990s. The insurance sector, composed of 15 domestic insurance companies including four life insurance companies and three larger companies that dominate the nonlife market, is the smallest sector in the financial system. The authorities monitor banks' long-term foreign exchange refunding needs and the outcomes of refunding operations.